The Cruise of the "Cachalot" Round the World After Sperm Whales - Bullen, Frank Thomas, 1857-1915 (Salt Lake City, UT : Project Gutenberg, 1998)
"The Cruise of the 'Cachalot' Round the World After Sperm Whales" by Frank T. Bullen is a narrative account of whaling adventures written in the late 19th century. The book offers a unique insight into the life of a sailor aboard a whaling ship, focusing on the author's experiences and the challenges faced in the South Sea whaling industry, particularly the pursuit of sperm whales. With vivid detail and a personal touch, Bullen aims to capture the often harsh realities of whaling, along with his reflections on shipmates and the perilous occupations they undertake. At the start of the narrative, the protagonist reflects on his journey from the streets of New Bedford to the whaling vessel Cachalot, where he becomes part of a diverse and rough crew. The opening chapters describe the recruitment process, detailing the motley group of men eager to set sail despite their ignorance of the whaling trade. Bullen conveys the chaotic and labor-intensive atmosphere aboard the Cachalot, highlighting the brutal treatment meted out by the officers and the challenges faced by the inexperienced sailors, or "greenies." This introduction sets the stage for Bullen's deep dive into life at sea, his developing camaraderie with his shipmates, and the dangerous work of hunting whales, promising a captivating exploration of a largely unfamiliar world. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Cruise_of_the_Cachalot
Release date is 1998-06-01
Produced by An Anonymous Volunteer, and David Widger
Keywords: Whaling -- Fiction; Sea stories; Sperm whale hunting -- Fiction; Whaling ships -- Fiction; Whalers (Persons) -- Fiction